Accuracy for determining sex of white‐tailed deer fetuses - Bronson K. Strickland; Stephen Demarais; Angeline Zamorano; Randy W. DeYoung; Chad M. Dacus (Wildlife Society Bulletin)
Abstract Explanations for variation in fetal sex ratio are needed to better understand the white‐tailed deer (Odocoileus virginianus) life‐history strategy. Sex determination in fetal white‐tailed deer is often based on external morphology and previous studies indicate that fetal sex does not become morphologically distinct until 63–69 days postconception. Until the advent of molecular techniques, there was no means to evaluate observer accuracy or to determine whether fetal sexing is feasible at <63 days postconception. We collected fetuses from wild deer in Mississippi, USA during spring 2008 (n = 55) and 2009 (n = 88) and measured fetal sex classification among 3 groups of observers with differing levels of experience: an inexperienced group (n = 31), an experienced group (n = 3), and a wildlife biologist group (n = 12). We then determined fetal sex using sex‐linked genetic markers and modeled observer accuracy using logistic regression. The inexperienced group required fetuses aged 63 days, 67 days, and 75 days old to correctly classify with 90%, 95%, and 99% accuracy, respectively. The experienced group correctly sexed fetuses at 54 days, 55 days, and 56 days old with 90%, 95%, and 99% accuracy, respectively. The wildlife biologists correctly sexed fetuses at 55 days, 57 days, and 59 days old with 90%, 95%, and 99% accuracy, respectively. Our study was the first to use known‐sex fetuses to estimate observer accuracy of fetal white‐tailed deer at various ages. Our results suggest training observers to recognize fetal tissue development can improve classification accuracy. © 2011 The Wildlife Society.